La planificación curricular y su incidencia en el desarrollo del pensamiento lógico en los niños de primer año de educación básica del Centro Infantil “Pío Jaramillo Alvarado” de la ciudad de Loja, período 2008-2009. Lineamientos alternativos - Torres Bustamante, Carmen Enid (2011)
In this master's work shows how logical thinking is in line with the planning that takes place in the kindergarten Pío Jaramillo Alvarado City of Loja. In this context, the work is divided into several stages: the first is devoted to the theoretical framework, which identifies the problem under study since the two variables: the development of logical thinking and curriculum planning. The next stage focuses on the methodology used to report which analyzes the used test called logical thinking of the Spanish author María del Pilar Ruesga Ramos, it was complemented by a survey of kindergarten teachers Pío Jaramillo Alvarado. The following discloses the results obtained through statistical processing of the recorded variables and analysis of the same, for better understanding statistical graphs has been busy. As a next step takes place the discussion about the findings taking into account both the responses of the children and teachers investigated to compare the relationship between the development of logical thinking and planning of teaching. The findings make note that there is an acceptable level of correspondence between planning and logical thinking of children with some limitations, so finally we propose some guidelines based through various exercises and games which aims to develop logical thinking children so that teachers take them into account in its future planning.